AB0888 ULTRASOUND FEATURES IN GOUT: A COMPARATIVE ANALYSIS WITH MATCHED CONTROL. (June 2019) - Silva, Joana; Faria, Daniela; Neves, Joana; Cerqueira, Marcos; Rodrigues, Joana; Azevedo, Soraia; Alcino, Sérgio; Tavares-Costa, José; Afonso, Carmo; Peixoto, Daniela; Teixeira, Filipa
Abstract : Background: Gout is a frequent inflammatory disease characterized by deposition of monosodium urate crystals in joints and tissues in the presence of hyperuricemia (1). Ultrasound (US) is a simple imaging technique that has gained interest in the assessment of individuals with gout due to its ability to identify inflammation and joint damage, as well as crystal deposition. The most characteristic gout US findings are the presence of intra-articular aggregates and the double contour (DC) signal, included in the 2015 ACR/EULAR classification criteria. Objectives: To identify potential differentiating US findings between individuals with gout and matched controls. Methods: A cross-sectional study was conducted, including 57 gout adult patients and 32 adult individuals with a normal uricemia, matched by age and gender. Sociodemographic, clinical and analytical data were collected. Bilateral US grey scale evaluation of the 1st metatarsophalangeal joint (MTP1), 2nd metacarpophalangeal (MCP2) and knee was performed in all participants. The following findings were assessed: intra-articular effusion, synovial hypertrophy, bone erosion, DC signal and intra-articular deposits. None of the participants presented with clinical signs of arthritis at the time of the evaluation. Results: The mean age of gout patients and healthy individuals was 63.3±12.6 and 63.8±10.5 years, respectively. The majority of the gout patients were male (87.7%), 77.2% had previous history of podagra and 26.3% had tophi. Mean disease duration was 4.3 years. Mean uricemia was 6.7±2.0 mg/dl in gout patients and 4.9±0.9 mg/dl in the control group. At the time of the study, 31 patients (54.4%) were treated with allopurinol, 9 (15.8%) with febuxostat, 1 (1.8%) with both allopurinol and febuxostat and 16 (28%) were not on urate lowering therapy. Comparatively to the control group, in the MTP1, patients with gout presented more frequently with synovial hypertrophy (26 vs 0, p<0.001), bone erosion (19 vs 0, p<0.001), DC signal (7 vs 0, p<0.05) and intra-articular aggregates (8 vs 0, p<0.05). At the knee, patients showed more often effusion (19 vs 2, p<0.001), synovial hypertrophy (26 vs 1, p<0001) and DC signal (8 vs 0, p<0.05). At the MCP2, only the presence of erosion was significantly more common in the gout group (8 vs 0, p<0.05). DC signal was found in 17 patients and in none of the healthy subjects (p<0.001); this finding was more frequently observed at the knee. There was an association between previous gout crisis in the MTP1 and the presence of erosion in this joint (p=0.04). An association was found between the presence of tophi and erosion (p<0.001), DC signal (p<0.05) and intra-articular aggregates (p=0.006). There was no association between uricemia levels, disease duration and the different US findings. Conclusion: In this study, the presence of synovial hypertrophy, erosions, DC signal and intra-articular deposits were the most frequent US findings in patients with gout. Moreover, these findings at the MTP1 joint allowed to distinguish between gout patients and matched control subjects. US seems to be useful to demonstrate evocative signs of crystal accumulation, inflammation or joint damage, even in the absence of overt arthritis. References: [1] Stewart S. et al. Ultrasound features of the first metatarsophalangeal joint in gout and asymptomatic hyperuricaemia: comparison with normouricaemic individuals. Arthritis Care (Hoboken) 2017 Jun; 69(6):875-883. [2] Neogi T. et al. Gout Classification Criteria: Na American College of Rheumatology/European League Against Rheumatism collaborative initiative. Arthritis Rheumatol 2015; 67:2557-68. Disclosure of Interests: None declared